E-resources usage among Polytechnic students in Southwest Nigeria: evidence from Federal Polytechnic, Ede and The Polytechnic, Ibadan Nigeria - Alasa, Sekinat Abiodun; Quadri, Ganiyu Oluwaseyi (International Journal of Knowledge Content Development & Technology, 2022)
This study examined e-resources usage among polytechnic students in Southwest Nigeria. Descriptive research design was adopted for this study and the population consisted of polytechnic students from The Polytechnic, Ibadan and Federal Polytechnic, Ede. They were 9671 students from both polytechnics. A multi-stage sampling technique was employed with a sample fraction of 5% was drawn from the total number of students in each faculty amounting to 381. A structured questionnaire was the major instrument used for data collection and the questionnaire were pre-tested using Cronbach-alpha to determine the reliability co-efficient. Data obtained was analyzed using SPSS. The study found that the students from both polytechnics are aware of the e-resources and that the e-resources were mainly used for research, class assignment and to update knowledge. Problem such as epileptic power supply, poor internet connection and so on were identified. The study concluded that polytechnic students could benefit immensely from the enormous usage of e-resources particularly for teaching, learning and research. Based on the findings, recommendations were made.